Study on Lapping Process of 304 Stainless Steel Using Tribochemical Fixed-Abrasive Lapping Platen - Su, Jianxiu; Zhang, Xiaofeng; Xue, Mingpu; Xiao, Wen; Zhang, Tianyi (Manufacturing Technology Journal, 2022)
Based on the previous research on the 304 stainless steel lapping and polishing in our research group, the tribochemical fixed-abrasive lapping platen for 304 stainless steel lapping and polishing were developed. The effects of the different pressure, the rotation speed, the lapping time and the abrasive size on the surface roughness and the material removal rate (MRR) were researched. It was concluded that when the abrasive size is 28 um, the lapping time is 15 min, the lapping speed is 90r/min, the lapping pressure is 27.580 KPa, and the maximum MRR is 412.524 nm/min. When the lapping time is 15 minutes, the rotating speed is 15 r/min, the lapping pressure is 13.790 KPa, the surface roughness Ra drops to 41nm. These findings show that the influence degree on the MRR from better to worse is the abrasive size, the lapping pressure, the rotation speed of the lapping platen and the lapping time. The order of the influence degree on the surface roughness from better to worse is the abrasive size, the rotation speed of the lapping platen, the lapping pressure and the lapping time. The results can give an important reference for next study on the tribochemical mechanical lapping of fixed-abrasive.
Keywords: Material removal rate; Surface roughness; Fixed-abrasive lapping; Tribochemistry; 304 stainless steel.